2018
DOI: 10.5539/gjhs.v10n7p128
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Cataract Surgery in Jordan

Abstract: PURPOSE: Cataract surgery is used for the removal of cloudy lens of eyes to reduce chances of blindness or any kind of visual impairments. The surgery is helpful to treat vision impairment, reduce chances of blindness, and bring positive impacts on quality of life among patients. The study aims to demonstrate key improvements in quality of life in terms of visual acuity and general quality of life after cataract surgery in Amman, Jordan.METHODS: The effect of cataract surgery on quality of life is assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“… 2 In a study conducted by Al-Zubi et al, the prevalence of cataract in Jordan was 37.8% among study participants. 3 Results from another study in Northern Jordan demonstrated that 46.7% of blindness usually occurs due to untreated cataract. 4 …”
Section: Introductionmentioning
confidence: 99%
“… 2 In a study conducted by Al-Zubi et al, the prevalence of cataract in Jordan was 37.8% among study participants. 3 Results from another study in Northern Jordan demonstrated that 46.7% of blindness usually occurs due to untreated cataract. 4 …”
Section: Introductionmentioning
confidence: 99%